Estrategias de comercialización para la quesería "SACA" Ubicada en el barrio Chanchalito. - Calvache Encalada, Alejandra Estefanía (2020)
The research project focused on proposing marketing strategies to generate an increase in sales of the "Quesería Saca" through the development of a marketing plan, which will reflect an increase in profitability, production and therefore allows generating new sources of employment in its sector of influence. The main problem that is related to the research is the low level of sales; it was created because of the innificient administration, the ignorance of the processes and procedures of suitable products, the high index of competition, and the wrong geographical location of the production plant among others. The methodology applied is quantitative-qualitative with the use of research techniques such as direct observation, interview with the owner, and surveys of stores that directly buy cheese products. The surveys carried out contributed positively to the project to detect several problems that the company has and determine the needs that customers have. The research will be used by the manager-owner to make decisions to increase sales and improve the business' position in the mind of the consumer through strategies focused on Marketing Mix (7p) that has been developed in the marketing plan, for example, the design of the product label, creation of sales points, improve the product portfolio, implementation of vacuum sealing among others. Finally, the financial analysis was carried out that allowed determining the economic benefits that the project will get technically, so the analysis of financial indicators such as TMAR was obtained with a result of 12.08%, VAN $1.033,18; TIR of 13.36% and the cost-benefit of the investment that the marketing plan will have for each dollar invested $0.22 profit. for execution.